2014
DOI: 10.3109/10903127.2014.942478
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Prehospital Ketamine for Control of Agitation in a Metropolitan Firefighter-based EMS System

Abstract: Introduction. Prehospital personnel frequently encounter agitated, combative, and intoxicated patients in the field. In recent years, ketamine has been described as an effective sedative agent to treat such patients; however, a paucity of research exists describing the use of prehospital ketamine. The objective of this study was to provide a descriptive analysis of the Columbus Division of Fire's experience with utilizing ketamine in the prehospital setting. We hypothesized that ketamine administration improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 18 publications
0
21
3
Order By: Relevance
“…Patients treated with ketamine experienced more side effects and more frequent intubations (25 [39%]) when compared with haloperidol (3 [4%]). Despite only nine patients having acute alcohol intoxication and none receiving an additional benzodiazepine, the intubation rate of 39% for ketamine in this study was higher than previous reports . This finding did not appear to be related to the dose, despite the authors not reporting a maximum ketamine dose.…”
Section: Literature Reviewcontrasting
confidence: 80%
See 2 more Smart Citations
“…Patients treated with ketamine experienced more side effects and more frequent intubations (25 [39%]) when compared with haloperidol (3 [4%]). Despite only nine patients having acute alcohol intoxication and none receiving an additional benzodiazepine, the intubation rate of 39% for ketamine in this study was higher than previous reports . This finding did not appear to be related to the dose, despite the authors not reporting a maximum ketamine dose.…”
Section: Literature Reviewcontrasting
confidence: 80%
“…This may be attributed to the rapid onset of action of ketamine, the shortened length of transit time (mean transit time 8 min), and the reduced baseline agitation compared with other studies because patients with profound agitation (score of 4+ on the AMSS) were excluded. Patients treated with ketamine experienced more side effects and more frequent intubations (25 [39%]) when 22,23 This finding did not appear to be related to the dose, despite the authors not reporting a maximum ketamine dose. All intubations occurred within the emergency department (ED), and most physicians cited the reason for intubation as an "unprotected airway not otherwise specified," followed by hypersalivation, refractory agitation, apnea, and aspiration or vomiting.…”
Section: Ketamine Versus Haloperidol Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite being used since the 1960s, ketamine has only recently been evaluated for use in treating agitation in the prehospital and ED settings and has been shown to be effective in controlling agitated patients in several studies. [22][23][24] However, research on the use of ketamine in the prehospital setting has demonstrated hypoxia, increased secretions, and laryngospasm requiring intubation following ketamine administration. [22][23][24][25] In one of the largest studies to date evaluating ketamine for prehospital agitation, ketamine performed well in comparison to haloperidol in controlling agitation but with an intubation rate of 39%.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies documenting ketamine's successful and safe use in the prehospital arena for multiple indications from analgesia, to sedation for excited delirium, to the most common use, sedation for endotracheal intubation [49][50][51][52]. One case report described delayed recurrent laryngospasm onset after arrival at the hospital in a patient who had received 500 mg (5 mg/kg) intramuscularly (IM) for excited delirium [53].…”
Section: Prehospital Usementioning
confidence: 96%